THE HADITH ON PARENTS’ RESPONSIBILITY IN CHILDREN’S EDUCATION: HADITH ON PARENTS’ RESPONSIBILITY IN CHILDREN’S EDUCATION: Hadith on Parents’ Responsibility in Children’s Education - Muhammad Yunus (Jurnal Diskursus Islam, 2025)
This research aims to understand and explore the teachings in the hadiths that explain the responsibilities of parents in educating their children, both in terms of morals, religion, and general education. The study seeks to raise awareness among the public, particularly parents, about the importance of providing balanced education to their children, both in academic aspects and in the development of character and religion. The methodology used in this research is Library Research. This research approach focuses on the collection, study, and analysis of existing literature, such as books, journal articles, papers, and other written sources. This methodology is used to explore information already available in the literature to understand the phenomena, theories, or issues being studied. The research shows that children whose parents are actively involved in their education tend to perform better in school, have higher self-confidence, and are better able to cope with life challenges. This involvement includes providing emotional support, helping children with assignments, and maintaining regular communication with teachers and school staff. Parents need to understand that children’s education is not solely the responsibility of schools, but also their responsibility as the first and foremost educators. Education should encompass moral, social, emotional, and intellectual aspects. Therefore, parents must give balanced attention to all these aspects.